2007
DOI: 10.1007/s10722-007-9282-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological variation in breadfruit (Artocarpus altilis (Park.) Fosberg) in the Western Ghats of India using AFLP markers

Abstract: Artocarpus altilis (Park.) Fosberg is an important fruit vegetable tree grown in the homesteads of southern part of India. To provide reasoned scientific management practices and conservation measures, the pattern of morphological and genetic variation were investigated for six populations using Amplified Fragment Length Polymorphism (AFLP) markers and 15 morphological traits. The use of five selective primer combinations on 60 samples resulted a total of 414 bands in which 85% were polymorphic. The values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…This expected result is possibly due to the neutrality of most AFLP markers, which are supposed to be less prone to environmental selection (Bruschi, Vendramin, Bussotti, & Grossoni 2000). It is also in agreement with earlier studies, for example by Sreekumar, Binoy, & George (2007) and Martínez, Cavagnaro, Masuelli, & Rodríguez (2003), who reported that genetic variation at AFLPs for Artocarpus altilis (Park.) Fosberg and Vitis vinifera L., respectively, was not reflected in quantitative morphological variables.…”
Section: Genetic Diversitysupporting
confidence: 91%
“…This expected result is possibly due to the neutrality of most AFLP markers, which are supposed to be less prone to environmental selection (Bruschi, Vendramin, Bussotti, & Grossoni 2000). It is also in agreement with earlier studies, for example by Sreekumar, Binoy, & George (2007) and Martínez, Cavagnaro, Masuelli, & Rodríguez (2003), who reported that genetic variation at AFLPs for Artocarpus altilis (Park.) Fosberg and Vitis vinifera L., respectively, was not reflected in quantitative morphological variables.…”
Section: Genetic Diversitysupporting
confidence: 91%
“…B. papyrifera has a wide distribution, but it is scattered in southwest China. Based on ISSR analysis, the overall genetic diversity is relative-ly high at the species level (PPB: 96%) compared with other Moraceae species, such as Ficus carica (PPB: 72.23%) (Salhi-Hannachi et al, 2006), Morus serrata (PPB: 67%) (Vijayan et al, 2004), Artocarpus heterophyllus (PPB: 22%) (Shyamalamma et al, 2008), and Artocarpus altilis (PPB: 85%) (Sreekumar et al, 2007). However, the genetic diversity is relatively low at the population level (PPB: 53.2%, H E : 0.1826, I: 0.2735).…”
Section: Genetic Diversity Of B Papyriferamentioning
confidence: 99%
“…Among many available DNA-based markers, AFLP markers are more reliable, yield a large number of markers per reaction, are cost-effective and have wide genome coverage (Prashanth et al, 2002;Hansen et al, 1999). AFLP markers have been successfully used, in the last decade, as a satisfactory alternative as well as compliment to morphological data in a variety of plant and tree species (Basha et al, 2007;Mahmud et al, 2007;Sreekumar et al, 2007). The purpose of the present study was to estimate the level of genetic diversity and to assess genetic relationships among 50 jackfruit accessions, collected from different parts of south India, using AFLP markers.…”
mentioning
confidence: 99%